2023
DOI: 10.1177/17454999231159469
|View full text |Cite
|
Sign up to set email alerts
|

Predicting adjustment of international students: The role of cultural intelligence and perceived cultural distance

Abstract: Despite years of investigation on international students’ adjustment, cultural distance and cultural intelligence, the definitions of and the relationship between these concepts are not yet sufficiently well established. This article further explores the three concepts and their possible interrelations. We propose a hypothesized model that considers subjectively perceived cultural distance (PCD) a variable of specific importance, and wherein we assume that the relationship between PCD and international student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…The specific focus on Chinese international students also means that the findings might not be applicable to students from other cultural backgrounds or to Chinese students within their own country, limiting the study’s broader applicability. In this sense, some previous studies showed a relevant role of perceived cultural distance in the complex pattern of relationships between Cultural Intelligence and international students’ adjustment ( Malay et al, 2023 ).…”
Section: Discussionmentioning
confidence: 86%
“…The specific focus on Chinese international students also means that the findings might not be applicable to students from other cultural backgrounds or to Chinese students within their own country, limiting the study’s broader applicability. In this sense, some previous studies showed a relevant role of perceived cultural distance in the complex pattern of relationships between Cultural Intelligence and international students’ adjustment ( Malay et al, 2023 ).…”
Section: Discussionmentioning
confidence: 86%
“…Other studies demonstrated that cultural differences have an impact on academic satisfaction, which is an important aspect of student satisfaction (Diener, 1995). However, there is one study found that perceived cultural distance can negatively affect the adjustment of international students (Malay et al, 2023). Based on this, this study proposes the fourth hypothesis.…”
Section: Literature Reviewmentioning
confidence: 87%